Outcomes registry for better informed treatment of atrial fibrillation II: Rationale and design of the ORBIT-AF II registry - Steinberg, Benjamin A. (2014)
BACKGROUND: Recent clinical trials have demonstrated the safety and efficacy of several non–vitamin K oral anticoagulants (NOACs) for the treatment of atrial fibrillation (AF). However, there are limited data on their use and outcomes in routine clinical practice, particularly among patients newly diagnosed as having AF and patients with AF recently transitioned to a NOAC. METHODS/DESIGN: ORBIT-AF II is a multicenter, national registry of patients with AF that is enrolling up to 15,000 newly diagnosed patients with AF and/or those with AF recently transitioned to a NOAC from 300 US outpatient practices. These patients will be followed for up to 2 years, including clinical status, outcomes (major adverse cardiovascular events, bleeding), and management of anticoagulation surrounding bleeding events. In addition, detailed data regarding the use of these agents in and around cardiac procedures, their complications, and management of such complications will be collected. CONCLUSIONS: The ORBIT-AF II registry will provide valuable insights into the safety and effectiveness of NOACs used in AF in community practice settings.